Detection of pap, sfa, afa, foc, and fim Adhesin-Encoding Operons in Uropathogenic Escherichia coli Isolates Collected From Patients With Urinary Tract Infection - Rahdar, Masoud (Jundishapur J Microbiol, 2015)
BACKGROUND: Uropathogenic Escherichia coli (UPEC) with its virulence factors is the most prevalent cause of urinary tract infection (UTI). OBJECTIVES; This study aimed to determine the occurrence of fim, pap, sfa, and afa genes among 100 UPEC isolates collected from patients diagnosed with UTI. MATERIALS AND METHODS: A total of 100 UPEC isolates were obtained from urine samples of patients with UTI. The prevalence of 5 virulence genes encoding type 1 fimbriae (fimH), pili associated with pyelonephritis (pap), S and F1C fimbriae (sfa and foc) and afimbrial adhesins (afa) were determined through PCR method. We also investigated the phylogenetic background of all isolates. In addition, the distribution of adhesin-encoding operons between the phylogroups was assessed. RESULTS: The prevalence of genes encoding for fimbrial adhesive systems was 95% for fim, 57% for pap, 16% for foc, and 81% for sfa. The operons encoding for afa afimbrial adhesins were identified in 12% of isolates. The various combinations of detected genes were designated as virulence patterns. The fim gene, which occurred in strains from all phylogenetic groups (A, B1, B2, and D) was evaluated and no significant differences were found among these groups. Conversely, significant differences were observed in relation to pap, afa, foc, and sfa operons. CONCLUSIONS: These results indicate that the PCR method is a powerful genotypic assay for the detection of adhesin-encoding operons. Thus, this assay can be recommended for clinical use to detect virulent urinary E. coli strains, as well as epidemiological studies.